REMUNERASI DIREKSI, DISPARITAS GAJI ANTAR DIREKSI DAN KINERJA PERUSAHAAN - Kirana, Candra Anindya; Novita, Nova (Jurnal Akuntansi Kontemporer, 2021)
Research Purposes. This research investigates the effect of directors' remuneration and pays dispersion among directors on firm performance. The study used a sample of non-financial services and insurance State-Owned Enterprises listed on the Indonesia Stock Exchange in 2015-2019. Research Methods. Data analysis technique used in this research is multiple regression. The firm performance is measured using the financial aspect health score, as stated in the Decree of the Minister of State-Owned Enterprises No. KEP-100 / MBU / 2002. The remuneration variable is measured using total remuneration. The pays dispersion between directors is measured using the average difference between the president director and other directors in the form of a percentage.Research Results and Findings. The test results show that directors' remuneration positively affects performance, while the pays dispersion between directors does not affect performance. These results indicate that the current regulations regarding the arrangements for BUMN directors' remuneration can reduce conflicts of interest of directors and prevent the negative impact of pays dispersion between directors.